1980
DOI: 10.1111/j.1365-4362.1980.tb01993.x
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Scabies in Turkey

Abstract: The epidemiology of scabies for the last twelve years has been studied in Turkey. Information was obtained from three regions (Istanbul, Ankara and Erzurum) having different climates. There has been an increase in scabies in the years following 1969 in Ankara and Erzurum and from 1967 on in Istanbul. It reached its maximum in 1978 in Erzurum, while this peak had been observed in early 1970s in other regions. Scabies incidence has significantly increased and decreased in winters and summers respectively, has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0
1

Year Published

1986
1986
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“…Many studies, in fact, have reported high incidences of scabies infestations during the cool weather of the fall and winter seasons [1, 25, 26]. As such, we further investigated the relationships between climate parameters and scabies infestations according to the different seasons.…”
Section: Discussionmentioning
confidence: 98%
“…Many studies, in fact, have reported high incidences of scabies infestations during the cool weather of the fall and winter seasons [1, 25, 26]. As such, we further investigated the relationships between climate parameters and scabies infestations according to the different seasons.…”
Section: Discussionmentioning
confidence: 98%
“…Probably, the reason for this was the crowded lifestyle of university students which increase in number, and immigrants placed in the city. In the epidemiological study conducted by Tüzün and his colleagues [15] in 1980, scabies was reported more commonly in males and in ages between 15-44 years. A finding of this study was that, as we observed, it peaked in the winter months.…”
Section: Discussionmentioning
confidence: 99%
“…It is rather difficult to explain these results. Almost all epidemiological studies on scabies (in United Kingdom [17,18], Denmark [19], Turkey [20], Israel [21,22], India [1] and New Zealand [23]) conclude that the incidence of this infestation is higher in autumn and winter. Only in a study carried out in Saudi Arabia it was observed that recurrence rate of scabies was higher from May to August [24].…”
Section: Discussionmentioning
confidence: 99%